UPAYA INDONESIA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN JEPANG KE INDONESIA TAHUN 2015-2017 - Lidia Melita; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The tourism sector is an important sector that earns foreign exchange for a country, including Indonesia, whose tourism sector plays an important role in its national economy. Japan is one of the second largest contributor countries in the East Asia region who visit Indonesia. In 2015-2017 Indonesia continued to experience an increase in the number of Japanese tourists from the previous three years. The achievement of the target of tourist visits can be seen from several efforts taken by Indonesia. Therefore this research was conducted to see how Indonesia's efforts to continue to increase Japanese tourist visits to Indonesia. This research used qualitative methods, with data collection techniques through literature studies sourced from books, journals, articles, and websites. This research uses the perspective of sociological liberalism and the theory of two level games. The results of this research indicates an increase in the number of Japanese tourist visits to Indonesia with several efforts implemented such as policies and cooperation that are not carried out by state actors alone but by non-state actors such as individuals, groups and organizations. The agreements made by Indonesia and Japan have an impact and result for both. Keywords: tourism, cooperation, Wonderful Indonesia, foreign tourists